INNV-09. CLINICAL EFFICACY OF TUMOR TREATING FIELDS FOR NEWLY DIAGNOSED GLIOBLASTOMA. (11th November 2019) - Liu, Yang; Strawderman, Myla; Warren, Kwanza; Richardson, Margie; Serventi, Jennifer; Mohile, Nimish; Milano, Michael; Walter, Kevin
Abstract: Recent clinical trials demonstrated that adding tumor treating fields (TTF) to radiotherapy and temozolomide chemotherapy (the Stupp protocol) increased survival for glioblastoma (GBM) patients. However, data is lacking on the magnitude of this survival effect when the regimen is used outside of a clinical trial as part of routine clinical practice. In the present study, we retrospectively identified adult patients with newly diagnosed GBM (n = 240) treated with the Stupp protocol at our institution from January 2005 to July 2017. We grouped patients into two time periods for comparison: 2005–2013 (group 1, Stupp protocol) and 2014–2017 (group 2, TTF+ Stupp protocol). Thirty-six percent (37/104) of patients in group 2 received TTF in conjunction with the Stupp protocol. Within group 2, the 37-patients who received TTF + Stupp had increased 6-month and 1-year survival rates compared to the 67-patients who received Stupp alone (97.1% vs. 75.7%, p = 0.006; 67.6% vs. 53.7%, p = 0.170, respectively). The improvement of survival rate at 6-month was further confirmed by a modified Poisson model (RR: 1.23, p = 0.010) adjusting for sex, age, performance status and extent of resection. However, we did not observe improvements in overall survival (OS) with a Cox model with TTF treatment modeled as a time-dependent covariate (HR = 0.87, p = 0.599). Furthermore, we did not find that the addition of TTF as a treatment option in our center significantly improved OS for patients in group 2 when compared to those in group 1 (429.0 vs. 395.0 days, p = 0.138). Therefore, while adding TTF to the Stupp protocol appeared to benefit patients with newly diagnosed GBM, this effect may be largely due to selection bias. Comprehensive studies including large number of patients as well as longer follow-up time are needed to validate our results.